The Jigsaw Technique on Students' Reading Comprehension across Learning Styles - Raudhatul Islam (Graduate Program, University of Islam Malang, 2020)
This research was conducted to investigate the effect of the jigsaw technique on reading comprehension with the students’ learning style. The aims of this research were to analyze whether the students who are taught by using jigsaw have better reading comprehension scores than taught by using conventional technique, to analyze whether the students who are different learning style have different reading comprehension scores and to analyze whether there is any interaction between jigsaw and learning style in students’ reading comprehension score. This research was quasi-experimental design with experimental and control groups of tenth grade of MA Zainul Hasan 4 Pakuniran. The instrument used questionnaire and reading comprehension test. This study used the independent t-test and two way ANOVA. The findings showed mean of experimental groups was 76.40 and control group was 68.00. Therefore, it meant that the students who taught by using jigsaw have better reading score than those who taught by using conventional technique. In accordance with second research problem, the significance value was .084. It meant the students who are different learning style have different reading comprehension scores. Concerning the third research problem, the result of the analysis of jigsaw and students’ learning style presented significance value was .319. It meant that there is no interaction between jigsaw technique and learning style in reading comprehension.